ENDOPHYTIC BACTERIA AS BIOFERTILIZERS FOR MAIZE (ZEA MAYS L.) - Y. K. JHALA; H. N. SHELAT; R. V. VYAS; D. G. PANPATTE (The Bioscan, 2014)
Total ten isolates of endophytic bacteria mainly belonging to genera Acetobacter and Azospirillum having higher nitrogen fixing efficiency were isolated from surface sterilized plant parts of different plant species using LGIP and NFB media selective for growth of Acetobacter and Azospirillum respectively. All the isolates can colonize maize endophytically under laboratory conditions. In vitro nitrogen fixation rates of all the isolates ranged from 4.0 to 36.3 mg N fixed / gm of sugar consumed among which isolate A 10 showed the highest N fixing capacity i.e. 36.3 mg /g of sugar. All the isolates were also capable of solubilizing tri calcium phosphate in Pikovskaya’s broth, the soluble phosphate content was found in the range of 1.19 - 21.0 μg/ml and 4.44-23.81 μg/ml at 3 and 5 DAI, respectively. Seed inoculation of all the isolates significantly influenced growth of maize cv. Narmada moti in lab and field conditions. The highest grain yield (5694 Kg/ha) was obtained when seeds were inoculated with isolate A 10 was applied alongwith 75% recommended dose (RD) of N fertilizer which was significantly superior as compared to 100 % RD of chemical N fertilizer sowing savings of 25% of Nitrogenous fertilizer through bacterization.